Stakeholder preferences about policy objectives and measures of pharmaceutical pricing and reimbursement. Issue 3 (September 2016) - Vogler, Sabine; Zimmermann, Nina; Habimana, Katharina
Abstract: Objective: Policy objectives, such as cost-containment and reward for innovation, can be conflicting, and different stakeholders are likely to prioritise policy measures with regard to their objectives differently. The study elicits preferences of different stakeholders in European countries about policy objectives and pharmaceutical pricing and reimbursement measures in accordance with their preferred objectives. Methods: Representatives of eight stakeholder groups (patients, consumers, competent authorities for pharmaceutical pricing and reimbursement, public payers, research-oriented industry, generic medicines industry, pharmacists, doctors) from the 28 EU Member States were invited to express their preferences about seven policy objectives and 16 measures in a web-based questionnaire. The replies were analysed through a Multi-Criteria Decision Analysis (MCDA), using an outranking method based on the ELECTRE III algorithm. Results: Based on 81 valid responses showed that nearly all stakeholders attributed highest priority to equitable access to medicines. Overall, stakeholders considered pharmaco-economic evaluation as the most appropriate policy measure to achieve policy objectives in accordance with their preferences. Value-based pricing and a transparent reimbursement process were ranked second and third. Across all groups, low preference was given to external price referencing (EPR) and co-payments, whereas stakeholders had differences in assessment on tendering, generic substitution and differential pricing. Conclusions: The overall negative assessment of the commonly used EPR policy suggests a possible need for change in current pricing practice. However, positions about alternative pricing options differ considerably across stakeholders. It is recommended to further explore the motivation of the stakeholders for their assessments in a qualitative research project. Highlights: We explored stakeholders' preferences on pharmaceutical policy goals and measures. Stakeholders gave highest priority to the goal of equitable access to medicines. Overall, stakeholders ranked pharmaco-economic evaluation highest. External price referencing was ranked last.